2016
DOI: 10.1590/0037-8682-0354-2015
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis caused by Sporothrix schenckii in an immunocompetent patient

Abstract: Sporotrichosis is the most common subcutaneous mycosis in South America and its association with zoonotic transmission remains a relevant public health problem in Rio de Janeiro, Brazil. The disease most commonly presents as subacute or chronic cutaneous lesions, although dissemination to various organs and systems occurs in rare cases, mainly in immunosuppressed individuals. This report describes a case of sporotrichosis with severe bone and subcutaneous damage in an immunocompetent patient who did not exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 10 publications
0
12
0
3
Order By: Relevance
“…Subsequently, in the majority of cases, nodules develop in the infection site leading to ulceration (Kauffman, 1999). Poorly controlled sporotrichosis can disseminate to distant anatomical sites, including bones, lungs, and central nervous system (Ferreira et al., 2016; Hassan et al., 2016; Rodrigues et al., 2016; Mialski et al., 2018). Apart from being a global health problem, sporotrichosis is hyperendemic in Brazil, mainly due to the zoonotic and crossed transmission of S. brasiliensis from infected felines (Montenegro et al., 2014; Sanchotene et al., 2015; Gremião et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, in the majority of cases, nodules develop in the infection site leading to ulceration (Kauffman, 1999). Poorly controlled sporotrichosis can disseminate to distant anatomical sites, including bones, lungs, and central nervous system (Ferreira et al., 2016; Hassan et al., 2016; Rodrigues et al., 2016; Mialski et al., 2018). Apart from being a global health problem, sporotrichosis is hyperendemic in Brazil, mainly due to the zoonotic and crossed transmission of S. brasiliensis from infected felines (Montenegro et al., 2014; Sanchotene et al., 2015; Gremião et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Gamaletsou Immunosuppression from hormone, chemotherapeutic agents used for oncologic and autoimmune diseases, hemodialysis and organ transplantation is a risk factor for mycosis. Immunodeficiency caused by HIV is another contributing factor [11][12][13][14][15][16][17]. The studies performed by the International Working Group on the Diabetic Foot showed that mycosis was detected along with bacterial flora in some diabetic patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Pathomorphological examination of biopsy sample at the nidus of purulent infection is the basic diagnostic criterion. Diagnostic biopsy can be produced as part of preoperative preparation of the patient [9][10][11][12][13][14][15][16][17]. Risk grading scale for mycosis was developed with the above factors in mind marking presence/absence of the signs in the right-hand column (Table 9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations